Evaluation Of Safety Awareness And Perception Of Wayfinding Tools Among Students And Staff In Engineering Campus, Universiti Sains Malaysia - Zamzuri, Muhammad Amir Hakimi Mohd (Universiti Sains Malaysia, 2022)
This dissertation examines safety awareness and perception of wayfinding tools among students and staff in Engineering Campus, Universit Sains Malaysia (USM). That focus is to investigate the understanding of students and staff about location of evacuation plans, emergency buttons, emergency exit sign, assembly area and evacuation route. A conducted survey with 185 respondents shows that the level of safety awareness and perception of wayfinding tools among students and staff in Engineering Campus, USM are good based on findings of this study. More precisely, a significant percentage of respondents know the sound of an emergency alarm (78.95%), know where to find the evacuation plan/map (74.2%), know where the emergency exits (90.9%) and know the assembly area to escape (91.85%). In terms of demographic differences, results from Mann Whitney U Test revealed that there is no significance difference in safety awareness and perception on wayfinding tools between males and females. Besides, experience in evacuation or safety education and training influences safety awareness and perception of wayfinding tools among student and staff in Engineering Campus, USM. This is because with experience and training in safety/evacuation, people will be more aware about safety and wayfinding tools compare to not experience people. Additionally, results from Kruskall-Wallis Test also show that no significance difference between age group and the level of educational background. The results of this study can assist university management in creating suitable strategies, design solutions, training, and educational campaigns for efficient and secure transfers. Moreover, the outcome is also a valuable resource in developing and verifying mathematical and theoretical models aiming to study students and staff’ evacuation in an emergency situation.